Bionic covert underwater communication focusing on the overlapping of whistles and clicks generated by different cetacean individuals. (1st December 2021) - Li, Chunyue; Jiang, Jiajia; Wang, Xianquan; Sun, Zhongbo; Li, Zhuochen; Fu, Xiao; Duan, Fajie
Abstract: Bionic camouflage covert underwater acoustic communication technology is playing an increasingly important role in the covert transmission of underwater information. Most cetaceans are group-living animals, and multiple cetaceans often appear in a specific ocean area at the same time. As a result, different cetacean individuals may generate whistles and clicks simultaneously, and the overlapping of whistles and clicks often appears in the received sound signals. Focusing on the overlapping characteristic of cetacean calls, this paper designs a bionic camouflage covert underwater acoustic communication method to improve the covertness and communication rate. The combined encoding through whistles and clicks overlapping of different cetacean individuals makes the constructed communication signals more in line with the characteristics of original cetacean calls, which improves the communication covertness. The pulse-to-pulse correlation and time delay difference encoding based on whistles and clicks are combined to improve the communication rate. Furthermore, the whistle signal processing algorithm based on time–frequency spectrogram image and morphology processing is utilized to separate the whistles and clicks in the received signals. And the whistle and click sequence are decoded, respectively. Finally, the bit error rates of the combined communication sequence, whistle sequence and click sequence are compared by conducting simulations. And the effectiveness, reliability and covertness of the proposed covert communication method are demonstrated through the simulations.